2023
DOI: 10.25081/jp.2023.v15.8387
|View full text |Cite
|
Sign up to set email alerts
|

Inselbergs: potential conservation areas for plant diversity in the face of anthropization

Abstract: Faced with the loss of biodiversity, particularly plant diversity, due to anthropogenic pressure, particular ecosystems such as inselbergs can constitute refuge areas. The objective of this study is to determine the conservation potential of plant biodiversity on inselbergs in Burkina Faso. A comparative study was carried out between inselberg’s vegetation and the surrounding plains vegetation. In each of these vegetation types, stratified and random sampling was adopted and data were collected in plots of 900… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(43 reference statements)
0
2
0
1
Order By: Relevance
“…The high value of Piélou's equitability index indicates the absence of species dominance in the various groupings described, both for savannah groupings and for grassland and pasture groupings. These high values also show that the plant communities of inselbergs in Burkina Faso are not subject to major disturbances [ 6 ]. showed that inselberg vegetation is less disturbed than vegetation on the surrounding plains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high value of Piélou's equitability index indicates the absence of species dominance in the various groupings described, both for savannah groupings and for grassland and pasture groupings. These high values also show that the plant communities of inselbergs in Burkina Faso are not subject to major disturbances [ 6 ]. showed that inselberg vegetation is less disturbed than vegetation on the surrounding plains.…”
Section: Discussionmentioning
confidence: 99%
“…[ [2] , [3] , [4] ]. Inselbergs are characterized by their isolation from the surrounding relief and their independence from the regional hydrological network [ 5 , 6 ]. Inselbergs are distinct ecosystems due to the nature of their substrate, and vegetation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malgré la précarité de leurs conditions microclimatiques et édaphiques très particulières (fortes insolations et évapotranspirations, plus ou moins existence de la couverture du sol), des études ont montrés que les inselbergs abritent une diversité floristique riche et caractéristiques en Côte d'Ivoire, en Guinée, au Bénin et au Burkina Faso (Kouassi et al, 2014;Tindano et al, 2015). De plus ces milieux constituent des refuges pour de nombreuses espèces végétales dans les régions à forte pression anthropique (Tindano et al, 2023b), et constituent des habitats particuliers aussi bien de par la nature de leur substrat que par la flore et la végétation. Certaines espèces végétales colonisent les inselbergs et sont associées à ce type de biotope du nord au sud du Burkina Faso.…”
Section: Introductionunclassified